Effect of Acetic Acid on Electrochemical Behavior of Sealed AA2319-T3 Al-Alloys Anodized in Phosphoric Acid Electrolytes - Rashid, Khalid H. (Al-Khwarizmi Engineering Journal, 2015)
Abstract The present study investigates the effect of acetic acid on corrosion behavior and its potential of hydrothermally sealed anodized AA2319-Al-alloys. Anodizing treatment was performed in stagnant phosphoric acid electrolyte with or without addition of acetic acid. Hydrothermal sealing was carried out in boiling water for each anodized specimen. The open circuit potential of the unsealed and sealed anodized samples was examined using open circuit potential measurement for the purpose of starting in scanning polarization diagrams. The potentiostatic polarization technique measurements were performed to assess corrosion behavior and sealing quality (i.e., degree of sealing) of the unsealed and sealed anodized aluminum. It was shown that the potentiostatic anodic and cathodic polarization of anodized aluminum was sensitive to degree of seal, which was more efficient in the case of anodized aluminum formed in acetic-phosphoric acid electrolyte mainly due to their higher corrosion potential and lower corrosion current, generally passes lower anodic and cathodic currents obtained at sealing exposure time 60 min. This suggests a specific role of the species on the sealed anodized aluminum surface coating, which contributes to the increasing of the performance in terms of corrosion improvement. The present study clearly validates the beneficial role of acetic acid in phosphoric acid anodizing baths for the corrosion protection of AA2319-Al-alloys. Keywords: Phosphoric Acid, Acetic Acid, Aluminum Alloy 2319, Anodizing, Polarization Technique.